The unusual suspect? The private sector in knowledge partnerships for agricultural and rural development - Chavez-Tafur, Jorge; Cummings, Sarah; Dentoni, Domenico; Kiwanuka, Suzanne; Körner, Jana; Seferiadis, Anastasia-Alithia; Staiger Rivas, Simone (2020)
The paper, ‘The private sector as the “unusual suspect” in knowledge brokering for international sustainable development: a critical review,’ draws on Glegg and Hoens’ (2016) meta-framework of knowledge brokering to analyse the role of the private sector in knowledge brokering in Europe and Africa. It establishes that the private sector’s roles are versatile, extending beyond connecting research evidence to potential users, to connecting researchers to funding opportunities, and to other researchers, and to hosting platforms. The private sector actively invests resources to facilitate knowledge uptake, although this is to a large extent driven by self-interest. Perceived self-interests remain a barrier to knowledge brokering with the private sector not always being see as a trusted partner.